Change in Loneliness Experienced by Older Men and Women Living Alone and With Others at the Onset of the COVID-19 Pandemic. (May 2022) - Wilson-Genderson, Maureen; Heid, Allison R.; Cartwright, Francine; Collins, Amy L.; Pruchno, Rachel
Building on theory suggesting that loneliness is distinct from living arrangements, social isolation, and perceived social support, we examined change in loneliness for older people at the onset of the COVID-19 pandemic. Analyzing 14-years of data with multilevel mixed-effects models, we found higher levels of loneliness among people living alone, people more socially isolated, and people with less perceived support. Gender affected changes in loneliness, controlling for social isolation, perceived support, living arrangements, age, education, income, health, and marital status. Women, whether living alone or with others, experienced increases in loneliness; women living alone reported the greatest increase in loneliness. Men living alone reported high levels of loneliness prior to the pandemic, but only a slight increase over time. These analyses, which demonstrate that loneliness changed at the onset of the pandemic as a function of gender and living arrangement identify older people most likely to benefit from intervention.